Receptor-independent modulation of TGF-β-induced pro-fibrotic pathways by relaxin-2 in human primary tubular epithelial cells - Grampp, Steffen; Goppelt-Strübe, Margarete (Cell and Tissue Research, 2018)
Renal tubular epithelial cells actively contribute to the development of renal fibrosis and may be targeted by anti-fibrotic drugs. Relaxin-2 (RLX2) applied as recombinant protein is suggested to be renoprotective. Therefore, we investigated whether human primary tubular epithelial cells (hPTEC) obtained from various donors were target cells for the anti-fibrotic actions of RLX2. Treatment of hPTEC with RLX2 reduced the TGF-β1-induced secretion of the pro-fibrotic factor CTGF (connective tissue growth factor) and inhibited fibronectin synthesis and secretion. Furthermore, metalloproteinase MMP2 secretion was increased, with no effect on MMP9. Considerable differences were observed between hPTEC obtained from different donors. Therefore, expression of the relaxin family peptide receptor RXFP1, the major mediator of renal RLX2 effects, was analyzed. A validated antibody detected a double band of 80–90 kDa in cellular homogenates by Western blotting. Expression of the detected protein was not altered by incubation with TGF-β1 and RLX2-induced modulation of CTGF expression did not correlate with the putative receptor expression. Therefore, relaxin family receptors RXFP1–4 were assessed by RNA-seq analysis. No evidence was found for mRNA expression of any of these receptors in several hPTEC preparations. Lack of RXFP1 mRNA was confirmed by qPCR using mRNA obtained from THP-1 cells as positive control. Our data thus provide evidence for primary renal human tubular epithelial cells as targets for the anti-fibrotic actions of RLX2. However, anti-fibrotic effects were observed at micromolar concentrations of RLX2 and shown to be independent of RXFP1 expression.
Created from Fastlane, Scopus look-up
Keywords: CTGF; Fibronectin; Human primary renal epithelial cells; MMP; Relaxin-2; RXFP1; Transforming growth factor beta